TAFSIR ASY-SYA'RAWI - MALKAN, MALKAN (ALQALAM, 2012)
This article tries to analyze the biography of Muhammad Mutawalli asy-Sya'rawi, a mufassir, along with its work Tafsir asy-Sya 'rawi: Khawatir asy-Sya'rawi haul al-Qur'an al-Karim. This article discusses the back ground of the emergence of this work, its sources, its method, its school (fiqh and theology), its characteristics, its interpretation, and the experts' opinion about him. The method used in analyzing this article is a critical-analytical method by using a historical approach. Based on its sources, Tafsir asy-Sya'rawi is the blend between Tafsir bi al-Ma'tsur and Tafsir bi al- Ra'yi, but the later one is more dominant. Based on its method, asy-Sya'rawi joins tahlili and maudlui methods, but the later one is more dominant. Based on its interpretation characteristics, he uses both tarbawi (education) and hida'i (guidance). Based on its school, he follows Syafi'i school in fiqh, and it is closed to Muktazilah School in theology. Based on its charactenstics, he has a specific characteristic that he proposes rational examples to support his interpretations. One of his interpretations is that he doesn't support mutasyabbihat and isra'iliyat interpretations, but he supports scientific interpretations (tafsir 'ilmi). Moreover, according to some experts, he is a rational, moderate, and sufistic ulama. Key words: Mutawalli asy-Sya'rawi, tafsir alQur'an, bi al-Ma'tsur and tafsir bi al-Ra'yi